ANALISIS BIAYA MEDIS LANGSUNG PASIEN BPJS BRONKOPNEUMONIA BALITA DI RAWAT INAP RUMAH SAKIT ISLAM SURABAYA ACHMAD YANI - Wardhani, Dewanti; Nita, Yunita; Rahem, Abdul (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Bronchopneumonia is a type of disease that attacks the lungs, often occurring in the bronchi and alveoli, which is caused by viruses, bacteria or fungi. Bronchopneumonia is the most frequently diagnosed infectious disease at the Surabaya Achmad Yani Islamic Hospital in 2022. The aim of the research is to determine the real direct medical costs of toddler bronchopneumonia and the components that make up real direct medical costs. The research uses an observational research design. Data collection was carried out in October 2023 by reviewing medical record data of patients who met the inclusion criteria during the period January 2023-March 2023. The research subjects consisted of 172 patients. The research results show that the real direct medical costs for toddler bronchopneumonia based on the perspective of the Surabaya Achmad Yani Islamic Hospital during the period January 2023-March 2023 are IDR. 463,267,781 with an average cost per patient of Rp. 2,693,417. The largest component of real direct medical costs is the component of use of hospital facilities at 34.87% and the component of costs for medicines and consumable medical materials at 34.06%. Cost analysis is very important so that patient treatment costs become more effective and efficient.